A comprehensive evaluation method for the site selection of new healthcare facilities in geological hazard-prone areas - Yu, Miao; Hu, Shi-yu; Cai, Jian-min; Guo, Peng-ning; Li, Hai-bo; Xing, Hui-ge (Frontiers in Earth Science, 2023)
Health care facilities in geological hazard-prone areas not only are responsible for local basic medical services but also are the main provider of hazard emergency rescue work. The selection of their sites is further complicated by the need to consider both the equalization of regional medical services and resource allocation and the impact of geological hazards on site safety. Shimian County in Sichuan Province, a geological disaster-prone area, was chosen as the study area. First, suitability analysis of the construction land was used to determine the site alternatives for new health care facilities, and an evaluation index system of construction land suitability consisting of geological hazard susceptibility, slope and aspect was established. Then, the suitability was evaluated by the Ordered Weighted Averaging (OWA) operator, and the Analytic Hierarchy Process (AHP) and the quantitative method of Regular Increasing Monotone (RIM) were used to calculate the criterion weights and order weights in the OWA operator respectively. The suitability results were classified into five levels: high, moderate, average, barely suitable, and unsuitable. Twelve site alternatives were identified in the highly and moderately suitable areas. Finally, a comprehensive evaluation index system consisting of indices such as construction land suitability and medical service accessibility was established, the PROMETHEE II method was conducted to comprehensively evaluate the site alternatives, and ranked results for the 12 site alternatives were obtained. These ranked results were analyzed by subindexes and Graphical Analysis for Interactive Aid (GAIA) to obtain a score for each alternative index and its similarity to the alternative, which could significantly help decision-making. This study achieves reasonable and scientific site selection for health care facilities in geological hazard-prone areas, and the results can provide references for relevant decision-makers.